Development of MoS2-ZnO heterostructures: an efficient bifunctional catalyst for the detection of glucose and degradation of toxic organic dyes. (7th December 2022) - Ali, Farhan; Zafar, Amina; Nisar, Amjad; Liu, Yanguo; Karim, Shafqat; Faiz, Faisal; Zafar, Zainab; Sun, Hongyu; Hussain, Shafqat; Faiz, Yasir; Ali, Tahir; Javed, Sofia; et al.
Abstract : The heterostructure catalyst MoS2 -ZnO possesses binary properties and provides a novel platform for the remediation of environmental as well as health issues. Abstract : To resolve the health and environmental issues related to the increase in diabetes and environmental pollution, development of an efficient and bifunctional catalyst is urgently required. For this prospective, the molybdenum disulfide–zinc oxide (MoS2 -ZnO) heterostructure has been scarcely investigated as a bifunctional catalyst. In this work, a heterostructured MoS2 -ZnO catalyst was synthesized and its electrocatalytic and photocatalytic properties were investigated. The heterostructure based modified glassy carbon electrode (MoS2 -ZnO/GCE) exhibits outstanding electrocatalytic properties for the detection of glucose. The electrode shows a reproducible sensitivity of 639.12 μA μM −1 cm −2 in a wide linear detection range from 0.025 to 6000 μM. Moreover, the electrode exhibits a low detection limit of ∼0.025 μM, excellent selectivity and long-term stability. In addition, the heterostructured MoS2 -ZnO shows excellent photocatalytic properties for the degradation of various toxic organic dyes i.e. rhodamine B (RhB), methyl blue (MB) and sandoz yellow (SY) under UV irradiation. The heterostructure demonstrates ∼97% degradation of MB, ∼78% of RhB and ∼81% of SY within 18 min of exposure. The photocatalytic efficiency of the heterostructure was found to be twice those of pristine MoS2 and ZnO, respectively. Our results reveal that the MoS2 -ZnO catalyst possesses binary properties by providing a novel platform for the remediation of environmental as well as health issues.